HOXA3 functions as the on-off switch to regulate the development of hESC-derived third pharyngeal pouch endoderm through EPHB2-mediated Wnt pathway - Fu, Yingjie; Zhang, Xueyan; Wu, Haibin; Zhang, Pingping; Liu, Shoupei; Guo, Tingting; Shan, Huanhuan; Liang, Yan; Chen, Honglin; Xie, Jinghe; Duan, Yuyou (Frontiers in Immunology, 2024)
Objectives: Normal commitment of the endoderm of the third pharyngeal pouch (3PP) is essential for the development and differentiation of the thymus. The aim of this study was to investigate the role of transcription factor HOXA3 in the development and differentiation of 3PP endoderm (3PPE) from human embryonic stem cells (hESCs).The 3PPE was differentiated from hESC-derived definitive endoderm (DE) by mimicking developmental queues with Activin A, WNT3A ， retinoic acid and BMP4. The function of 3PPE was assessed by further differentiating into functional thymic epithelial cells (TECs). The effect of HOXA3 inhibition on cells of 3PPE was subsequently investigated.Results: A highly efficient approach for differentiating 3PPE cells was developed and these cells expressed 3PPE related genes HOXA3, SIX1, PAX9 as well as EpCAM.3PPE cells had a strong potential to develop into TECs which expressed both cortical TEC markers K8 and CD205, and medullary TEC markers K5 and AIRE, and also promoted the development and maturation of T cells. More importantly, transcription factor HOXA3 not only regulated the differentiation of 3PPE, but also had a crucial role for the proliferation and migration of 3PPE cells. Our further investigation revealed that HOXA3 controlled the commitment and function of 3PPE through the regulation of Wnt signaling pathway by activating EPHB2.Our results demonstrated that HOXA3 functioned as the on-off switch to regulate the development of hESC-derived 3PPE through EPHB2-mediated Wnt pathway, and our findings will provide new insights into studying the development of 3PP and thymic organ in vitro and in vivo.